Vidro arqueológico da Casa Gouveia (Èvora): do vidro romano ao vidro industrial - Ferreira, Manuela Almeida (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
In 1998, when this article was achieved, few Modern Times glassware − the more impressive group of these finds − had been recovered yet from Portuguese archaeological urban sites. The finds from Évora date from Roman times (1st-century to late Empire) till the 20th-century (pressed glass). Hence the interest of this publication, especially in what concerns the drinking glasses and the pharmaceutical devices of the 16th-and 17th-centuries.